A prospective study of cervical length measurement in predicting preterm delivery - Norlidar, Mohamed (2008)
To study the cervical length measurement in relation to the outcome of pregnancy.All patients who attended HUSM antenatal clinic and those who are fulfilled all the criteria listed are recruited in this study. The participants involved will be subjected for transabdominal and transvaginal ultrasound at 16-20, 24, 28 and 32 weeks period of gestation for cervical length measurement. At 28 week of gestation, high vaginal swab will be taken and then subsequently, they will be having a routine antenatal follow up as scheduled like the other patients who are not involved in this study till time of delivery.A total of 183 pregnant women have been recruited in this study where 61 of them had preterm labour. The incidence of preterm delivery in this study was about 33.3%. Patients with history of previous preterm delivery, miscarriage and short cervix were predisposed to preterm delivery. In general, the average cervical length at 16 weeks, 24 weeks, 28 weeks and 32 weeks are 2.82 em,2.78 em, 2.73 em and 2.69 em respectively. Both TVS and TAS in measuring the cervical length showed significant association in predicting preterm delivery. At a cut off point of s 2.5 em, transvaginal cervical length showed PPV of 100% in all gestation in this study except at 32 weeks to predict preterm delivery and was far by superior compared to T AS. Transvaginal ultrasound at 28 weeks demonstrated the highest predictive value compare to other gestation in predicting preterm delivery.Cervical length measurement can be used as an important predictor for preterm delivery where the length of the cervix is inversely related with risk of preterm labour. In predicting preterm delivery, the measurement of cervical length by TVS is more superior than T AS .